2023
DOI: 10.1186/s12902-022-01209-x
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of vitamin D supplementation on glycemic control in people with type-2 diabetes: a systematic review and meta-analysis of randomized controlled trails

Abstract: Background There is conflicting evidence on the effect of vitamin D on glycemic control. Therefore, in the current meta-analyses, we aimed to assess the effect of vitamin D supplementation on the glycemic control of type 2 diabetes (T2D) patients. Methods We conducted a comprehensive search in electronic databases including; PubMed/Medline, Web of Science, Scopus, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), and NIH’s Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…al. found that vitamin D supplementation was associated with reduced HbA1c when participants were vitamin D deficient at baseline [66]. Thus, prior findings have indicated conflicting results regarding the therapeutic effects of vitamin D on glycemic control, especially regarding optimal dosage and duration.…”
Section: Discussionmentioning
confidence: 99%
“…al. found that vitamin D supplementation was associated with reduced HbA1c when participants were vitamin D deficient at baseline [66]. Thus, prior findings have indicated conflicting results regarding the therapeutic effects of vitamin D on glycemic control, especially regarding optimal dosage and duration.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency is also correlated with other factors, such as DM duration, iron concentration, and renal function assessed by eGFR. A recent systematic review and meta-analysis of 46 randomized clinical trials showed that vitamin D supplementation reduced the HbA1c up to 0.2%, the beneficial effect on glycemic control being more intense in T2DM patients with 25(OH)D deficiency [ 48 ]. The relationship between age and lower values of vitamin D may be explained by the reduced mobility of the elderly and, therefore, their inability to be exposed to the sun.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical and basic studies indicated that vitamin D might exert beneficial effects on the symptoms or the prevention of T2DM [14,16,17,32]. Furthermore, a latest metaanalysis suggested the beneficial effects of vitamin D on the con- trol of blood glucose in patients with T2DM and the prevention of diabetic complications [33]. However, the application of vitamin D in the prevention and treatment of T2DM remains controversial and the understanding of the anti-T2DM mechanisms of vitamin D is still lacking.…”
Section: Discussionmentioning
confidence: 99%